2014
DOI: 10.1093/ntr/ntu180
|View full text |Cite
|
Sign up to set email alerts
|

Out of Sight and Out of Mind? Evaluating the Impact of Point-of-Sale Tobacco Display Bans on Smoking-Related Beliefs and Behaviors in a Sample of Australian Adolescents and Young Adults

Abstract: Our findings suggest an immediate impact of display bans on youth's exposure to tobacco pack displays, and likely impacts on smoking-related outcomes. These results suggest that removing tobacco displays from retail environments can positively contribute to the denormalization of smoking among youth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
52
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 31 publications
4
52
0
Order By: Relevance
“…This finding has important public health implications, given that tobacco availability and promotion at the POS is ubiquitous in many jurisdictions. Together with evidence that newly implemented POS display bans reduce youth smoking susceptibility and denormalise smoking,37 38 our results strongly indicate that legislation banning tobacco POS promotion will effectively reduce smoking among young people.
What this paper adds

Two systematic reviews have found consistent evidence of a positive association between exposure to point-of-scale (POS) tobacco promotion and increased risk of smoking, particularly in relation to smoking susceptibility among children and adolescents.

No meta-analysis has been conducted on these studies.

The odds of having tried smoking are around 1.6 times higher for children and young people frequently exposed to POS tobacco promotion, compared with those who are less frequently exposed.

…”
Section: Discussionsupporting
confidence: 61%
“…This finding has important public health implications, given that tobacco availability and promotion at the POS is ubiquitous in many jurisdictions. Together with evidence that newly implemented POS display bans reduce youth smoking susceptibility and denormalise smoking,37 38 our results strongly indicate that legislation banning tobacco POS promotion will effectively reduce smoking among young people.
What this paper adds

Two systematic reviews have found consistent evidence of a positive association between exposure to point-of-scale (POS) tobacco promotion and increased risk of smoking, particularly in relation to smoking susceptibility among children and adolescents.

No meta-analysis has been conducted on these studies.

The odds of having tried smoking are around 1.6 times higher for children and young people frequently exposed to POS tobacco promotion, compared with those who are less frequently exposed.

…”
Section: Discussionsupporting
confidence: 61%
“…This view corresponds to a previous study (Dunlop et al, 2015) which suggests that the display bans on cigarettes in retail environments could contribute to the denormalisation of smoking among young people.…”
Section: Experiences Of Display Bansupporting
confidence: 91%
“…Moreover, while a partial tobacco advertising restriction operates in Korea, a comprehensive ban on tobacco advertising had been enforced in Australia. Also, a display ban of tobacco products had been implemented in Australia with limited exemptions (Dunlop et al, 2015;The Cancer Council, 2017). In contrast, tobacco displays and advertising in retail environments are still allowed in Korea (Cho, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…3 Several studies suggest that point of sale advertising affected smoking cessation and stimulated impulse purchasing among smokers. [17][18][19][20] The exposure to tobacco brands imagery stimulated physical craving and resurrected the emotional ties that they had with "their" brand among lapsed quitters and former smokers. 21 Cigarette pack displays may also function to undermine quitting intention among established smokers.…”
mentioning
confidence: 99%